HUBUNGAN KEKUATAN MENGGENGGAM DENGAN FLEKSIBILITAS EKSTREMITAS ATAS PADA LANSIA - Zahra Beatrissa Putri Bantolo (2022)
Elderly is the final stage of a someone's existence cycle and undergoes the growing old technique with changes in diverse physical, mental, and social factors. Changes that occur in the musculoskeletal system are a lower in muscle mass, weakened muscle strength and lower muscle flexibility. A lower in muscle strength can cause a decrease in functional ability while a decrease in muscle flexibility in the elderly will have a prime effect on the performance of the movements that occur. The purpose of this examine became to determine the relationship between grip strength and upper extremity flexibility in the elderly. This study uses a descriptive correlation research with a cross sectional model. The measuring instrument used to measure grip strength is the Hand Grip Dynamometer and to measure the flexibility of the upper extremities is the Back Scratch Test, and a sample size of 35 elderly people in the Dahlia Senja Community. The data analysis used is univariate and bivariate analysis. The results of research that has been carried out using the Spearman Rho correlation test method may be concluded that there's no relationship among grip strength and upper extremity flexibility in the elderly. The conclusion is suggested with a larger number of samples and a more precise research screening, to be able to find a wider range of respondents' characteristics which are expected to be wider.